Efficient Production of Single‐Walled Carbon Nanotube Aqueous Dispersion Using Hexahydroxytriphenylene as a Dispersant and Stabilizer. Issue 22 (11th June 2018) - Liu, Gang; Liu, Neng; López‐Moreno, Alejandro; Zhao, Ping; Dai, Wubin; Shi, Shengwei; Komatsu, Naoki
Abstract: Dispersing single‐walled carbon nanotubes (SWNTs) is one of the key technologies for promoting the practical application of SWNTs in many fields. Herein, we report on an efficient dispersant, 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene, for dispersing SWNTs through noncovalent functionalization. Typically, 68 wt% of the initial SWNTs (25 mg/L) were well dispersed in water at the low concentration of hexahydroxytriphenylene (25 mg/L). In order to compare the efficiency of various dispersants, we propose mole‐ and weight‐based dispersing efficiency index ( m ‐ and w ‐DEI, respectively) based on the concentration of the dispersant employed (Cm‐DPS mmol/L or Cw‐DPS mg/L) and the concentration of the SWNTs dispersed (Cd‐CNT mg/L); m ‐ and w ‐DEI are defined as Cd‐CNT / Cm‐DPS and Cd‐CNT / Cw‐DPS, respectively. Although a biopolymer shows slightly better m ‐DEI than hexahydroxytriphenylene, the w ‐DEI of hexahydroxytriphenylene is better than that of all the dispersants we compared. For example, the m ‐ and w ‐DEI of hexahydroxytriphenylene are much better than those of sodium dodecylbenzenesulfonate (SDBS), one of the most widely used dispersant for SWNTs, by two and three orders of magnitude, respectively. The large difference of the DEI between 2, 3, 6, 7, 10, 11‐hexahydroxytriphenylene and SDBS is found to be supported by the difference in their association constants ( Ka ) for the complexation with SWNTs, which were determined by the recently reported titration method. Abstract : 2, 3, 6, 7, 10, 11‐Hexahydroxytriphenylene works as an exfoliant and dispersant to give a stable aqueous dispersion of single‐walled carbon nanotubes. The dispersant is found to exhibit higher dispersing efficiency index (DEI) than various kinds of dispersants reported so far.